Quality of life and functional outcome following microsurgical fasciocutaneous vs. myocutaneous tissue transfer - Dlugos, Yvonne Denise; Lahoda, Lars-Uwe; Vogt, Peter M.; Altintas, Mehmet Ali (GMS German Plastic, Reconstructive and Aesthetic Surgery – Burn and Hand Surgery, 2017)
Background: Coverage of soft tissue defects at the lower extremity may necessitate microsurgical tissue transfer, such as by fasciocutaneous anterolateral thigh (ALT) or myocutaneous musculus latissimus dorsi (MLD) flaps. Hitherto, these two flaps have not been compared systematically in terms of patient satisfaction and functional outcome. The purpose of this study was to compare patients’ satisfaction and functional outcome following ALT vs. MLD transfer. Methods: Thirty-six patients were divided into an ALT group (n=22, mean age: 42.0 years) and a MLD group (n=14, mean age: 55.5 years). Both groups were compared concerning isokinetic analysis (Biodex System III), circumference measurement, flap volume, scar size, complication rates, patients’ satisfaction, and functional outcome (SF-36 questionnaire, Foot and Ankle Outcome Score (FAOS)), hospital stay and duration of surgery.Results: Isokinetic force measurements showed a higher mean maximum force for dorsiflexion in the MLD group at an angular velocity of 60°/sec. (ALT 17.5±7.9 Nm, MLD 18.5±16.3 Nm; p<0.013) and higher strength endurance at 180°/sec (ALT 8.17±5.6 Nm, MLD 13.36±9.4 Nm; p<0.008), whereas no differences in all other measurements was found. The mean lower leg circumference was significantly larger in the MLD group (ALT 25.0±3.39 cm, MLD 30.36±2.14 cm; p<0.013). The mean difference in the circumference measurement between the covered and uninjured extremity within both groups differed significantly (ALT 2.55±1.71 cm, MLD 8.13±1.65 cm; p<0.001). The flap size in the ALT group was 148.77±6.58 cm² compared to 251.63±21.28 cm² in the MLD group (p<0.01). The scar size in the ALT group was 40.61± compared to 93.40±22.65 cm² in the MLD group (p<0.01). Superficial necrosis occurred in both groups (ALT n=3, MLD n=5). Donor area seroma was only seen in the MLD group (n=2). A complete flap failure was recorded only in the ALT group (n=2). SF-36 and FAOS indicated no significant differences between groups (p>0.05) in quality of life and functional outcome. Average hospital stay and duration of operation showed no differences between groups.Conclusion: In the present study, no significant differences in quality of life and functional outcome were found between ALT and MLD group. Only in isokinetic force measurement isolated significant differences with advantages of MLD group were detected. The current study provides additional information concerning ALT and MLD flaps and may support decision-making in selecting the appropriate free flap.